Avaliação da resposta inflamatória de lesão medular em ratos produzida pelo modelo experimental de transecção - ALBUQUERQUE, Rafaela Pontes de (2019)
The traumatic injury of the spinal cord affects thousands of people worldwide, causing neurological deficits with partial or total loss of sensory/motor ability. There are still no therapies that completely restore function after a spinal cord injury, and may be related to the cascade of events that increase the local inflammatory reaction, leading to the progressive destruction of the neuronal tissue, which end up affecting its spontaneous regeneration and functional recovery. Thus, this research evaluated the tissue inflammatory response of the spinal cord in rats submitted to spinal cord injury by complete spinal cord transection through morphological characterization. We used rats of the species Rattus norvegicus (albinus variety) of the Wistar lineage, 60-day-old male adults, from the Central Bioterium of the Federal University of Maranhão (Universidade Federal do Maranhão – UFMA). The animals were divided into two experimental groups: control (rats without surgical procedure); and injured (rats submitted to the surgical procedure of laminectomy with complete spinal cord transection). After 48 hours of the surgical procedure, motor assessment was performed through the Basso, Beattie and Bresnahan (BBB) scale, and only animals that scored 0-2 were used. After the period of 3, 7, 14 and 21 days after surgical procedure, the animals were euthanized and their injured spinal cords were removed for histotechnical processing (histology, scanning microscopy and immunohistochemistry using the antibodies NOX2, anti-CD43, anti-GFAP) for better evaluation of the tissue inflammatory response. It can be concluded that the spinal cord injury produced by the experimental model used in this research reproduces, homogeneously, the severe functional, sensory and motor disability, with a great clinical relevance, as it induced inflammatory, demyelinating and progressive histopathological changes, which were intensified with time after spinal cord injury.